BIO-BIBLIOGRAPHY OF DR. VÍCTOR HUGO ACUÑA ORTEGA-COSTA RICAN HISTORIAN - Alvarado Barrientos, Vanessa (2013)
This essay introduces a bio bibliography of Costa Rican historian Víctor Hugo Acuña Ortega. Its objetive is to rescue Acuña Ortega’s work as a historian in order to offer an important seconday source for otther researchers.